PDGF-B Can Sustain Self-renewal and Tumorigenicity of Experimental Glioma-Derived Cancer-Initiating Cells by Preventing Oligodendrocyte Differentiation - Yiwen Jiang; Maria Boije; Bengt Westermark; Lene Uhrbom (Neoplasia: An International Journal for Oncology Research, 2011)
According to the cancer stem cell (CSC)/cancer-initiating cell hypothesis, glioma development is driven by a subpopulation of cells with unique tumor-regenerating capacity. We have characterized sphere-cultured glioma-derived cancer-initiating cells (GICs) from experimental gliomas induced by platelet-derived growth factor-B (PDGF-B) in neonatal Gtv-a Arf-/- mice. We found that the GICs can maintain their stem cell-like characteristics in absence of exogenous epidermal growth factor and fibroblast growth factor 2 and that this culture condition was highly selective for tumor-initiating cells where as few as five GICs could induce secondary tumor formation after orthotopic transplantation. Addition of FBS to the medium caused the GICs to differentiate into cells coexpressing glial fibrillary acidic protein and Tuj1, and this differentiation process was reversible, suggesting that the GICs are highly plastic and able to adapt to different environments without losing their tumorigenic properties. On inhibition of virally transduced PDGF-B by small interfering RNA treatment, the GICs stopped proliferating, lost their self-renewal ability, and started to uniformly express CNPase, a marker of oligodendrocyte precursor cells and mature oligodendrocytes. Most importantly, PDGF-B depletion completely abrogated the tumor-initiating capacity of the GICs. Our findings suggest that interfering with PDGF-controlled differentiation could be a therapeutic avenue for patients diagnosed with the PDGF-driven proneural subtype of human glioblastoma.